EKSPLORISASI MEDIA PEMBELAJARAN MATEMATIKA BERBASIS GAME - Prestisdiva, Hazima Najla; Kusuma, Anggun Badu (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2023)
The purpose of the researcher is to explain what is used in game-based learning media. This study uses a systematic review method, namely Systematic Literature Review. Researchers collect journal articles sourced from the Google Scholar database. The articles collected are only articles published in the 2020-2022 timeframe. Online game-based math learning media consists of Quizizz, Kahoot, and Wordwall. This platform is used as a medium for conveying learning material. Meanwhile, traditional game-based mathematics learning media consists of marbles and dakon. This learning media is used to train children's abilities in thinking, calculating, social intelligence, and logical mathematical intelligence. This traditional game-based mathematics learning media can increase student activity, student learning outcomes, and student interest.